Transformation Of Islamic Law Into National Law: Model, Problem And Alternative Solution Of Practicing Sharia In Indonesia - Syarif, Nurrohman (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Abstract In the hands of some Muslims who make religion an ideology, sharia must be realized in real life in society through political instruments that can provide force. However, in their struggle, some of them use only one interpretation and one model, so it is difficult to be compromised. Base on assumption that there is more than one model, this research aims to formulate :1) some models of transformation of Islamic law into national law, 2) the problems 3) alternative concepts of solutions, and 4) the impact of any policy taken by the state. This research is a kind of non-doctrinal qualitative legal research. Data was obtained from the books or literature and it is analyzed to see the correlation between legal substance, legal structure and legal culture. This study concluded that without being Islamic state, there many models that can be used by Indonesian Muslims in transforming or practicing sharia. Keywords: Islamic state, politics, religion, secular state